Determination of four main components of gentamicin in animal tissues after solid‐phase extraction by high‐performance liquid chromatography/tandem mass spectrometry. (12th September 2018) - Zhang, Congcong; Hu, Jian; Sun, Fengmei; Jia, Man; Chen, Gang; Wu, Cuiling; Zheng, Lufei
Abstract : Rationale: An analytical method for gentamicin in animal tissues was developed and validated. An alkaline mobile phase with an HPH C8 column was selected so that all the four gentamicin components were retained and eluted without using fluorinated ion‐pairing reagents. Methods: The method is sufficiently sensitive and highly selective, using a strong cation‐exchange solid‐phase extraction cartridge (PCX) to clean up the samples. Different types of solid‐phase extraction columns and membranes were considered to obtain a high recovery. The method was validated on spiking samples, recovery, inter‐ and intra‐assay variation, to ensure its accuracy and precision. Results: The LOQ (S/ N  ≥ 10) for gentamicin in goat meat, liver, kidney and adipose tissue was 25, 50, 30 and 30 ng/g, respectively; the LOD (S/ N  ≥ 3) was 5, 10, 10 and 10 ng/g, respectively. The recoveries were between 88% and 106%. The method in all animal tissues was calibrated from 10 to 1000 μg/L in the matrix‐assisted standard solution. Conclusions: The novelty of this method is that the commonly used fluorinated ion‐pairing reagent was not used in the mobile phase in our analysis, greatly reducing the contamination of the ESI source in negative mode. Moreover, the four gentamicin components were clearly separated via chromatographic separation.